Safety and efficacy of prednisone versus placebo in short-term prevention of episodic cluster headache: a multicentre, double-blind, randomised controlled trial. Issue 1 (January 2021) - Obermann, Mark; Nägel, Steffen; Ose, Claudia; Sonuc, Nilüfer; Scherag, André; Storch, Peter; Gaul, Charly; Böger, Andreas; Kraya, Torsten; Jansen, Jan-Peter; Straube, Andreas; Freilinger, Tobias; et al.
Summary: Background: Prednisone is commonly used for initial short-term therapy of episodic cluster headaches before preventive medication such as verapamil becomes effective, but this strategy has not been tested in large randomised trials. We aimed to access the safety and efficacy of this treatment approach. Methods: This study was a multicentre, randomised, double-blind, placebo-controlled trial done in ten specialised headache centres in Germany. Patients with episodic cluster headaches who were aged between 18 and 65 years and within a current pain episode for not more than 30 days, received 100 mg oral prednisone for 5 days followed by tapering of 20 mg every 3 days, or matching placebo (17 days total exposure). All patients received oral verapamil for long-term prevention, starting with 40 mg three times daily and increasing to 120 mg three times daily by day 19; patients then continued with verapamil 120 mg throughout the study. Randomisation was computer-generated at a 1:1 ratio by use of an interactive web-response system, with stratification according to age, sex, and participating site. Participants, investigators, and those assessing outcomes were unaware of treatment allocation. The primary endpoint was the mean number of attacks within the first week of treatment with prednisone compared with placebo. An attack was defined as a unilateral headache with moderate-to-severe intensity of at least five on a numerical rating scale. All efficacy and safety analyses were done in the modified intention-to-treat (mITT) population, which consisted of all patients who had been randomly assigned to a trial group and received at least one dose of prednisone or placebo. The study was stopped early due to slow recruitment and expired funding. The study was registered with EudraCT (2011–006204–13) and with the German Clinical Trials Register (DRKS00004716). Findings: Between April 5, 2013, and Jan 11, 2018, 118 patients were enrolled in the study. Two patients dropped out immediately and 116 patients were randomly assigned (57 patients to prednisone and 59 patients to placebo); 109 patients were included in the mITT analysis (53 patients assigned to prednisone and 56 patients assigned to placebo). Participants in the prednisone group had a mean of 7·1 (SD 6·5) attacks within the first week compared with 9·5 (6·0) attacks in the placebo group (difference −2·4 attacks, 95% CI −4·8 to −0·03; p=0·002). Two serious adverse events occurred, both in the placebo group (inguinal hernia and severe deterioration of cluster headache). A total of 270 adverse events were observed: in the prednisone group, 37 (71%) of 52 patients reported 135 adverse events (most common were headache, palpitations, dizziness, and nausea) and in the placebo group, 39 (71%) of 55 patients had 135 adverse events (most common were nausea, dizziness, and headache). Interpretation: Oral prednisone was an effective short-term preventive therapy in our population of patients with episodic cluster headache. Our findings support the use of prednisone as a first-line treatment in parallel to the up-titration of verapamil, although the efficacy of prednisone alongside other long-term prevention requires additional investigation. Funding: German Federal Ministry for Education and Research.